Long term results of endoscopic dilatation for corrosive oesophageal strictures. - Broor, S L (1993)
Although dilatation is the treatment of choice for most patients with benign oesophageal strictures, there is little information on its efficacy and safety in corrosive oesophageal strictures. Of 123 adults with benign oesophageal strictures treated by endoscopic dilatation, 52 (42.3%) had strictures after corrosive ingestion and 39 (31.7%) had peptic strictures. Treatment was considered adequate if the oesophageal lumen could be dilated to 15 mm and there was complete relief of dysphagia. If dysphagia recurred after adequate initial dilatation, the stricture was dilated again up to 15 mm. Initial dilatation was adequate in 93.6% of patients with corrosive strictures and this success rate was comparable with that of the peptic stricture group (100%, p > 0.05). Long term success after adequate initial dilatation was studied in 36 patients with corrosive strictures (mean follow up 32.36 (17.12) months, range 6-60) and 33 patients with peptic strictures (mean follow up 36.32 (17.9) months, range 6-60). The mean (SEM) number of symptomatic recurrences per patient month during the total follow up period in the corrosive group was significantly higher than that in the peptic group (0.27 (0.04) v 0.07 (0.02), p < 0.001). The recurrence rate in the corrosive group, however, decreased over time, and after 12 months it was significantly (p < 0.001) lower than the recurrence rate in the first six months. After 36 months, the difference in the recurrence rate in the two groups was not significant (p > 0.05). Only nine oesophageal perforations occurred during a total of 1373 dilatation treatments (procedure related incidence 0.66%), and eight of these were in the corrosive stricture group. These patients were managed conservatively and subsequently strictures were dilated adequately in all. Endoscopic dilatation is safe and effective for short and long term relief of dysphagia in patients with corrosive oesophageal strictures.